The Relationship between Elderly Exercise and Sleep Quality in the Elderly in the Elderly Exercise Group at the Kedaton Inpatient Health Center, Bandar Lampung City in 2024 - Nadhifa, Anggitha; Sulastri, Diah; Maryuni, Sri (CV. Rayyan Dwi Bharata, 2024)
One of the changes in organ systems during the degeneration process is the elderly's nervous system which can cause sleep problems. Exercise and activity levels can have an clash on an individual's capacity to sleep as well as the quality of their sleep. The purpose of this study is to ascertain whether senior exercise and senior sleep quality at the Kedaton inpatient health center. Quantitative research and Cross Sectional research design. Research analysis includes univariate and bivariate. Uses the chi square test to connect 2 variables independent and dependent variables.There is a significant relationship between exercise for elderly and sleep quality for the elderly at the Kedaton Inpatient Health Center, Bandar Lampung City with statistical results obtained with a p value of 0.005 or p value α (0.05). Suggestions for future researchers It is required to see again at the possibility as other activities that help enchane the sleep quality of the elderly.